2017
DOI: 10.1080/07315724.2017.1330162
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Folic Acid Therapy in Patients with Hyperhomocysteinemia

Abstract: More than 40% patients with HHcy failed to reach the normal range (5-15 μmol/L) after 3 months of folic acid supplementation. Further prospective studies are warranted to explore the reasons for failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Currently, folate supplementation is the primary intervention in HHcy therapy, which can effectively reduce plasma Hcy in China. 5 In our preliminary research, 6 the Hcy levels of over 40% of patients were still higher than 15 μmol/l after 90 days of 5 mg/day folate intervention.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Currently, folate supplementation is the primary intervention in HHcy therapy, which can effectively reduce plasma Hcy in China. 5 In our preliminary research, 6 the Hcy levels of over 40% of patients were still higher than 15 μmol/l after 90 days of 5 mg/day folate intervention.…”
Section: Introductionmentioning
confidence: 71%
“…Compliance was assessed by telephone interview at 45 and 90 days of follow‐up. Our preliminary study found that there was significant difference in the effective rate among 858 HHcy patients (175 cases who lost to follow‐up or with poor compliance were excluded) with good and moderate compliance . Subjects were divided into the success group (Hcy < 15 μmol/l) and failure group (Hcy ≥ 15 μmol/l) according to the reviewed Hcy levels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the formation mechanism of HHcy, the current expert guidelines recommend folic acid and vitamin B12 supplementation for treatment [8][9][10][11][12], but meta-analysis results show that folic acid supplementation for more than three years is necessary to reduce the risk of stroke [13].…”
Section: Introductionmentioning
confidence: 99%
“…At home and abroad, the results of the study on supplementation of folic acid to reduce Hcy concentration were inconsistent (13)(14)(15) . A previous study found that more than 40 % patients with HHcy failed to reach the normal level after folic acid supplementation (16) . These may be caused by genetics.…”
mentioning
confidence: 99%